Performa F1 antara Ayam Sentul X Kampung dan Ayam Pelung X Sentul pada Umur 0-12 Minggu - Sopian, Y.; Darmati, S.; Sumantri, C. (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2015)
The experiment aimed to observe growth performance of 3 native chicken crossed. The materials used in this experiment were 22 day old chick (DOC) resulted of natural mating between male pelung and female sentul chicken (PS) and 113 DOC resulted of natural mating between male sentul and female kampung chicken (SK). Feeds were given during experiment divided into 3 phases that were BR-21E 100% for chicken between 0-3 weeks of age, rice bran 20% and BR-21E 80% for 4 week age, and grower feeds rice bran 40% and BR-21E 60% for chicken between 5-12 weeks. Variables which recorded weekly were body weight until 12 weeks of age, weight gain, feed consumption, feed conversion, and mortality. The t-test was used to compare data of performance between two sexes and between two cross system (PS and SK). The results showed that body weight at 12 weeks of crossbred (PS) male was significantly higher than SK (P<0.01) also female (P>0.05). Feed consumption and feed conversion were not significantly different (P>0.05). The mortality rate during the experiment were 4.54% for crossbred PS and 7.07% for SK. SK and PS can be applied to increase meat production.